Peran Kecerdasan Buatan dalam Inovasi Instrumen Keuangan Hijau untuk Pembangunan Berkelanjutan - Giovanni, Axel; Dewantara, Ghiyats Furqan; Musthafa, Afif; Hartono, Budi; Putri, Namira Rahma; Fadlilah, 'Atikah Nur; Witantri, Galuh; Kurniasari, Erika (TIN: Terapan Informatika Nusantara, 2025)
Climate change is driving the urgency of transitioning to a low-carbon economy. In this regard, green finance is an important instrument in mitigating climate change. However, the implementation of green finance faces challenges such as data complexity, information asymmetry, and the risk of greenwashing. This study aims to systematically examine the role of artificial intelligence (AI) in expanding the adoption, effectiveness, and innovation of green finance instruments among stakeholders. The method used is a Systematic Literature Review (SLR) of 61 articles from the Scopus database, analyzed using the PICo framework and CASP quality assessment. The results of the study indicate that AI can fundamentally support 1) stakeholder needs and challenges, 2) accuracy, transparency, and efficiency, and 3) mitigating the risk of greenwashing. Stakeholder needs and challenges can be addressed by AI through improved accuracy in risk prediction and market analysis, as well as optimizing green portfolios. AI mechanisms have proven capable of improving accuracy through advanced predictive models, strengthening transparency with Explainable AI (XAI) and blockchain, and driving efficiency through automation and resource optimization. Significantly, AI integration strengthens the positive impact of sustainable investments and serves as a powerful mitigation tool against greenwashing risks by objectively verifying environmental claims and enhancing accountability. AI emerges as a transformative technology to accelerate an effective and credible green financial ecosystem.